Diagnostic and therapeutic care pathway of the Cardiac Network for Heart Failure - Pasquale Palmiero; Matteo Durante; Maria Maiello; Valentina D’Andria; Cosima Caputo; Lucia Giordano (Italian Journal of Medicine)
The Cardiac Network for Heart Failure integrates patients into a dedicated clinical pathway to enhance care and improve quality of life, creating a personalized approach according to current guidelines. This study seeks to evaluate nurses’ familiarity with health literacy tools and assessment scales in managing chronic heart failure to improve patient outcomes and reduce hospital readmissions through a survey on health literacy tools and assessment scales. Our findings underscore the need for continuous education through regular training on scales and health literacy tools. Enhanced structured health education is essential, with nurses requiring additional time and resources to focus on patient education strategies beyond symptom management. Encouraging the use of innovative technologies, such as multimedia tools and digital platforms, could improve the quality and frequency of educational interventions, addressing time constraints faced by healthcare staff. Increasing follow-up frequency, ideally to at least monthly, could improve patient monitoring and reduce hospital readmissions. Greater awareness and commitment among nurses are critical for effectively managing chronic heart failure. Targeted training and additional resources are necessary to address existing gaps, ultimately improving patient care and outcomes.